Technology and Contractions: Evidence from Manufacturing - SAMANIEGO, Roberto M. (Institutional Knowledge at Singapore Management University, 2015)
Theory suggests a range of technological characteristics that might interact with the business cycle depending on what kind of shocks or propagation mechanisms are quantitatively important. We use variation in industry growth within manufacturing to determine which technological characteristics interact significantly with the business cycle. We find that growth in labor intensive industries is especially sensitive to contractions. We show this cross-industry asymmetry occurs specifically in contractions, not in recoveries nor over the cycle in general.